2012
DOI: 10.5114/ninp.2012.32099
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced tumours of meninges. Report on eight cases and review of the literature

Abstract: Radiation-induced tumours of the meninges show certain characteristic histopathological features, which may promote invasiveness of the tumour and higher risk of malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…These events usually occur many years after the exposure. Several studies showed a latent period of 24–38 years, depending on the age at exposure, the dose levels, and the tumor type (Kunert, Matyja, Prokopienko, & Marchel, ; Schneider et al, ). Occasionally such an exposure was described to be associated with multiple tumors, rarely fulfilling NF2 diagnostic criteria (1/3,013 cases) (Sznajder et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These events usually occur many years after the exposure. Several studies showed a latent period of 24–38 years, depending on the age at exposure, the dose levels, and the tumor type (Kunert, Matyja, Prokopienko, & Marchel, ; Schneider et al, ). Occasionally such an exposure was described to be associated with multiple tumors, rarely fulfilling NF2 diagnostic criteria (1/3,013 cases) (Sznajder et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The 1920s provided the first reports of post-radiation sarcomas in patients, demonstrating evidence of the carcinogenic effects of radiation. 5,6 Following these reports, Cahan subsequently developed the original criteria for the diagnosis of a post-radiation malignancy (specifically sarcoma). This has most recently been revised by Al-Mefty et al 7 specifically for use with meningiomas and summarized in their manuscript as Table 1 (reproduced here): 1.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor must not be present prior to radiation therapy The most frequent intracranial tumors resulting from irradiation are meningiomas, gliomas and sarcomas. 5 Postradiation meningiomas are the most commonly reported radiation-induced neoplasms reported in the literature and there is some suggestion of increasing incidence due to the expanding indications for radiation therapy and increasing longevity of patients after radiation therapy. 5,7 The risk of developing a meningioma in post-radiation patients is described as 6-10× higher than the standard population.…”
Section: Introductionmentioning
confidence: 99%
“…4) (Kunert et al 2012;Mansouri et al 2014;Madden et al 2010). In the study of Kunert et al, 2 % of meningiomas were associated with previous radiation treatment (c) Contrast-enhanced imaging confirms the classical appearance of meningiomas; the frontal lesion was histologically confirmed (Kunert et al 2012). The average time after initial treatment was 24 years, and some of the patients developed multiple tumors which was described as a common feature by Mansouri et al (2014) and is also found in our presented case.…”
Section: Imaging Findings After Radiation Of the Brainmentioning
confidence: 99%
“…Although rare, the most common induced tumors are meningiomas (Fig. 4) (Kunert et al 2012;Mansouri et al 2014;Madden et al 2010). In the study of Kunert et al, 2 % of meningiomas were associated with previous radiation treatment (c) Contrast-enhanced imaging confirms the classical appearance of meningiomas; the frontal lesion was histologically confirmed (Kunert et al 2012).…”
Section: Imaging Findings After Radiation Of the Brainmentioning
confidence: 99%